Noise Reduction Scheme for High-speed Low-floor Tram Seating Areas - PAN Minkai; CHEN Yunsha (Chengshi guidao jiaotong yanjiu)
[Objective] With the increasingly wide application scenarios of low-floor trams, new high-speed low-floor trams have emerged to meet the market demands for higher operating speed. To ensure that high-speed low-floor trams can maintain good noise performance while increasing the operating speed, it is necessary to carry out research on the optimization of the whole vehicle noise scheme. [Method] Based on the FE (Finite Element)-SEA (Statistical Energy Analysis) method, a SEA model of the whole vehicle is established, and the vehicle interior noise is simulated and predicted through acoustic software. Based on the simulation and prediction results, combined with the actual structure of the under-vehicle space, a noise reduction scheme for the seating area is proposed, a sound insulation simulation calculation and an optimization research on the whole vehicle noise scheme are carried out. [Result & Conclusion] In terms of the whole vehicle interior noise, when the train is running at a constant speed of 100 km/h, the interior noise does not meet the requirements of the design target. The maximum noise value is located at a height of 1.2 m in the middle car, and the main sound source comes from the wheel-rail noise, and the sound energy is transmitted into the carriage mainly through the gangway floor and the bogie areas. By optimizing the angle of the stiffener plate and the thickness of the panel, the weighted sound insulation amounts of Profile 2 and Profile 3 can be increased by 3.3 dB and 5.1 dB respectively. If the panel thickness is further increased, the weighted sound insulation amounts of Profile 4 and Profile 5 can be increased by 4.3 dB and 6.4 dB respectively. Based on the optimization scheme of the profile parameters and the floor section, the optimized vehicle interior noise can meet the requirements of the interior noise limit.